SPEECH ERRORS IN A TALK SHOW PROGRAM OF METRO TV FACE TO FACE WITH DESI ANWAR BROADCASTED IN JANUARY TO JUNE 2012 - Farida Indri Wijayanti (Universitas Muhammadiyah Surakarta, 2012)
This article explores the types of speech errors, the frequency of each type of speech error, the dominant of speech error, and the sources of speech errors in the talk show program of Metro TV Face to Face with Desi Anwar broadcasted in January to June 2012. Descriptive and library research are applied as method. The data are utterances containing speech errors produced by guest speakers. The method of collecting data is documentation. Investigator triangulation is used by cross checking the findings or the interpretation of data with expert judgment in order to strengthen the validity. The technique for analyzing data is error analysis. The results show that there are 253 utterances containing 428 speech errors which are derived from 9 types of speech errors based on Clark and Eve, Gleason and Ratner, and Poulisse theory. The distribution of each type of error is started by 143 filled pauses (33.41%). The number of speech errors comprises of 121 repeats (29.88%), 49 slips of the tongue (12.10%), 39 retraced false starts (9.63%), 18 corrections (4.44%), 18 unretraced false starts (4.44%), 17 interjections (4.20%), 12 silent pauses (2.96%), and 11 stutters (2.72%). From the frequency of the speech errors, it can be drawn that the most dominant error is filled pause. The speech errors are mostly caused by three sources; they are cognitive difficulty, situ- ational anxiety, and social reasons.